Morphology and molecular phylogeny of two new species of Spirostrombidium (Ciliophora, Oligotrichia), with a key to the species of Spirostrombidium. Issue 8 (17th November 2018) - Wang, Rui; Song, Wen; Yi, Zhenzhen; Al-Rasheid, Khaled A. S.; Hu, Xiaozhong
Abstract : Microscopic methods were used to investigate the morphological characterization of two novel oligotrich ciliates, Spirostrombidium paraurceolare sp. nov. and Spirostrombidium faurefremieti sp. nov., isolated from a mangrove wetland in Zhanjiang and an intertidal sandy beach in Qingdao, respectively. Spirostrombidium paraurceolare sp. nov. is characterized by three thigmotactic and 8–10 buccal membranelles, the girdle kinety spiralling around cell with one and a half whorls, and located at right anterior third of dorsal side anteriorly. Spirostrombidium faurefremieti sp. nov. can be recognized by a prominently deep and broad buccal cavity, two thigmotactic and 15–19 buccal membranelles, and the girdle kinety spiralling around cell with two whorls. The small subunit ribosomal RNA genes of these two species were sequenced and compared with those of their congeners to reveal nucleotide differences. Phylogenetic analyses revealed that the genus Spirostrombidium is non-monophyletic. Spirostrombidium faurefremieti sp. nov. falls into a clade comprising most congeners, but Spirostrombidium paraurceolare sp. nov. branches off and groups with Varistrombidium kielum with moderate support. A key to the identification of Spirostrombidium species is also provided.www.zoobank.org/urn:lsid:zoobank.org:pub:AB96BEE6-BE3A-4B95-B75A-3469B1C53ABB2